Analysis of the Use of Animated Videos on YouTube in Asking and Giving Opinion at UPTD SMP Negeri 2 Gunungsitoli Utara: English - Sara Riska Zebua; Nursayani Maru’ao; Hidayati Daeli; Riswan Zega (Journal of English Development, 2025)
This study aims to describe the use of Animated Videos on YouTube in learning Asking and Giving Opinion and its benefits for class VIII B students at UPTD SMP Negeri 2 Gunungsitoli Utara in the 2024/2025 school year. In the context of Merdeka Belajar Curriculum, learning media such as Animated Videos has an important role in increasing student engagement and facilitating interactive learning. Based on previous research, Animated Videos are effective in helping students understand complex concepts and improve communication skills. This research uses a qualitative approach with descriptive method to analyze data obtained through interviews, questionnaires, and documentation. Based on the results of the interview, the teacher used an Animated Video video posted by Betterfly English entitled Expressions of Asking for and Giving Opinions which can be accessed for free on YouTube (link: https://www.youtube.com/watch?v=LYXUC2K2bQk) Overall, the results of the study show that the use of YouTube Video Animation supports students' understanding of Asking and Giving Opinion material significantly, as well as making learning more interesting and fun.